Indikator Keuangan yang Memengaruhi Kinerja Keuangan Koperasi Simpan Pinjam Sejahtera Kementrian Agama Kabupaten Luwu - Agusalim Sunusi; Sukmawati Sultan Sahrir (Fakultas Ekonomi, Universitas Muslim Indonesia, 2022)
This study was based on the phenomenon which shown that the return on Equity (ROE) of USP KPRI Sejahterah Ministry of Religious Affairs of Luwu Regency, 2007 – 2021 has fluctuated. This study used the Liquidity proxied by the Current Ratio, the Capital Structured proxied by the Debt toEquity Ratio and the Efficiency proxied by the Efficiency Ratio, as the Independent Variable and the Financial Performance proxied by Return on Equity (ROE) as the Dependent Variable. This research was conducted to know the influence of Liquidity, Capital Structure and Efficiency on Financial Performance of USP KPRI Sejahterah Ministry of Religious Affairs of Luwu Regency, 2007 – 2021. The data this research was Secondary Data of Financial Report from USP KPRI Sejahterah Ministry Religious Affairs of Luwu Regency 2007 – 2021, which has been approved in General Annual Meeting. This research used Multiple Linear Regression Analysis to analize the influence of Independent variable to Dependent variable and using Purposive Sampling Technique in determining the research sample. The result of analysis shown that the Liquidity proxied by Current Ratio partially had a negative did not significant effect on the Financial Performance, the Capital Structure proxied by the Deb to Equity Ratio partially had a positive and significant effect on the Financial Performance and Efficiency of the company proxied by Efficiency Ratio partially had a negative and significant on the Financial Performance. Based on partial analysis, Capital Structure variable was the dominant variable affecting Financial Performance (ROE) KSP KPRI Sejahterah of Ministry Religious Affairs of Luwu Regency.